Thinking About Psychology : The Science of Mind and Behavior - Blair-Broeker, Charles T. ; Ernst, Randal M. and Myers, David G. (New York Worth Publishers, 2003)
"This book will be an ally for teachers striving to ignite a passion in their students for psychology's many relevant findings, and for students wanting to satisfy a growing curiosity about themselves, their families, their friends, and the world of people around them."
Include Index, Appendix, Glossary, References and Illustration
Keywords: Psychology